Potential Essential Oil Local Medicine Plant From West Aceh As Repellency Against Rice Weevils (Sitophilus oryzae) - Oviana Lisa; Sumeinika Fitria Lizmah; Siti Aminah; Putri Mustika Sari (Universitas Labuhanbatu, 2026)
Background: The Increased rice production will cause pest problems in storage warehouses. This pest attack can damage rice and reduce quality. The longer and thicker the stack of rice, the greater the number of rice weevil pests will appear and affect the quantity and quality of the rice itself. To overcome this problem, natural control can be carried out using medical plant as repellent so as not to damage the environment or the quality of stored rice. Based on the active compounds found in lime leaves, citronella, and marigold’s leaves, research is needed to determine the repellent activity of essential oils from citronella, lime, and marigold’s leaves against rice weevil (S. oryzae). Methodology: The method used in this research is a factorial Completely Randomized Design (CRD) experimental method with two factors and three replications. The implementation of the research was consists of Sitophilus oryzae Test Pest Propagation, Medicinal Plant Sample Preparation, Essential Oil Repellent Activity Test Using Rice, and Data Analysis using Two-Ways ANOVA with Post-hoc Tukey HSD 5%. Results: The result showed that the concentration of essential oils from Marigold, lime, and citronella leaves affected the percentage of rice weevil repellent. At a concentration of 100%, the essential oil extracted from marigold leaves exhibited lower repellent activity (90%) compared to the essential oil derived from lime leaves (94%) and citronella leaves (92%). On the other hand, the duration of the observation period did not significantly affect the repellency activity of essential oils derived from lime leaves, citronella leaves, or marigold leaves. The concentration of essential oils from Marigold, lime and citronella leaves on the best percentage of rice weevil repellent was 100% with the repellency percentage above 90%. Contributions: These findings indicated that essential oils derived from these medical plants have potential as environtmentally friendly repellents for controlling rice weevil infestations in stored rice